Endovascular Treatment of Isolated Iliac Artery Aneurysms with Anaconda Stent Graft Limb - Christos Karathanos; Elias Kaperonis; Dimitrios Xanthopoulos; Theophanis Konstantopoulos; Maria Exarchou; Caterini Loupou; Vassilios Papavassiliou (Case Reports in Vascular Medicine)
Isolated aneurysms of the iliac arteries are relatively rare conditions that traditionally have been treated by surgical reconstruction. We report our experience with endovascular treatment of iliac artery aneurysms (IAAs) with Anaconda stent graft limb. Two male patients were found to have 4.5 and 3.6 cm isolated common IAAs, respectively. The endograft was successfully advanced and deployed precisely to the intended position in both cases. In one case the internal iliac artery was embolized. No type I or II endoleak was observed immediately after the procedure. In one patient postimplantation fever (>38°C) and gluteal claudication occurred. After 2 years followup both iliac endovascular stent grafts are patent and without endoleak. Endovascular treatment with Anaconda limb stent graft seems to be a safe and feasible alternative to open surgery.